21y=(20y+-30)

Simple and best practice solution for 21y=(20y+-30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21y=(20y+-30) equation:


Simplifying
21y = (20y + -30)

Reorder the terms:
21y = (-30 + 20y)

Remove parenthesis around (-30 + 20y)
21y = -30 + 20y

Solving
21y = -30 + 20y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-20y' to each side of the equation.
21y + -20y = -30 + 20y + -20y

Combine like terms: 21y + -20y = 1y
1y = -30 + 20y + -20y

Combine like terms: 20y + -20y = 0
1y = -30 + 0
1y = -30

Divide each side by '1'.
y = -30

Simplifying
y = -30

See similar equations:

| 4(a+4)+2a-4= | | 8(x-1)+7=6x+2(-2+x) | | 5(3n+4)=7(7n+1)+7 | | 5x+6+13x+30=180 | | -3(2t-4)+2t=3t-4 | | -2(6x-5)+3=-12x+13 | | 8(x+7)-4=52 | | -17+29=-3(x+7) | | 2k+6=2(k+3) | | 0.8(3x+9)=4.3-(x-3) | | 7(2x+1)=2x-6x | | 2(3x+5)=-44+18 | | 7k-12-3k=2(2k-6) | | 3.6x+53.9=20.3-13.2x | | 1/6y-6=-5 | | y=13x-1 | | -6.7-4z-8.1-2z=-5z-3.4 | | 4r+4=14r+6 | | 6(m-2)-3=10m+1-4m | | 5r+8=26r+15 | | -14(y+3)+6(3y-7)=3(y-3)+12 | | (2m-1)x^2+(1+m)x+1a=2 | | 10.333s^3-58.8s-210=0 | | 5z-7=6z-2z | | Y=1/2(4-2)(4-8) | | 2m+1.50=6.50 | | Y=1/2(3-2)(3-8) | | Y=1/2(2-2)(2-8) | | 36=6y+3 | | 15/75 | | -t^2-12t-24= | | f(6)=20x+14 |

Equations solver categories